2007
DOI: 10.1152/ajprenal.00288.2005
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinedione ameliorates renal injury in experimental diabetic rats through anti-inflammatory effects mediated by inhibition of NF-κB activation

Abstract: Thiazolidinedione (TZD), a ligand for peroxisome proliferator-activated receptor-gamma (PPAR-gamma), exerts anti-inflammatory effects independently of the insulin-sensitizing effect. In the present study, we tested the hypothesis that TZD prevents the progression of diabetic nephropathy by modulating the inflammatory process. Five-week-old Sprague-Dawley rats were divided into three groups: 1) nondiabetic control rats (non-DM), 2) diabetic rats (DM), and 3) diabetic rats treated with pioglitazone (DM+pio). Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(138 citation statements)
references
References 45 publications
6
129
2
1
Order By: Relevance
“…25,26,75,76,80,81 At the same time, it has been reported that NF-kB activation induces TGF-b production. [82][83][84] Thus, there is a potential positive feedback mechanism between TGF-b production and NF-kB activation that enhances the fibrotic process. (vi) Furthermore, we used RT-qPCR and protein detection by western blot to demonstrate that H 2 O 2 induces the expression and secretion of TGF-b1 and TGF-b2, and it has been clearly demonstrated that TGF-b1 and TGF-b2 induce the conversion of ECs into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,75,76,80,81 At the same time, it has been reported that NF-kB activation induces TGF-b production. [82][83][84] Thus, there is a potential positive feedback mechanism between TGF-b production and NF-kB activation that enhances the fibrotic process. (vi) Furthermore, we used RT-qPCR and protein detection by western blot to demonstrate that H 2 O 2 induces the expression and secretion of TGF-b1 and TGF-b2, and it has been clearly demonstrated that TGF-b1 and TGF-b2 induce the conversion of ECs into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Sobel et al (15) reported that, in BARI 2D subjects, IS as opposed to IP treatment led to changes in biomarker profiles that were indicative of a profibrinolytic, antithrombotic, and antiinflammatory state. Peroxisome proliferator-activated receptors are widely expressed in the kidney, and peroxisome proliferator-activated receptor gamma agonists have renoprotective effects in experimental models of diabetic kidney disease (16,17). Administration of TZDs to insulin-deficient and -resistant diabetic rats ameliorated albuminuria and histologic hallmarks of diabetic nephropathy (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Decreases hypertrophy of kidney in diabetic mice [74] 6) NF-κB p50 nuclear translocation is decreased [75] 7) PARP-1 Inhibition prevents NF-KB/AP-1 binding at MMP-9 promoter. Hyperglycaemia induced PARP activation plays important role in pathogenesis of glomerulopathy associated with T2DM and could serve as novel therapeutic target.…”
Section: ] Parp Inhibitors [74757677]mentioning
confidence: 99%
“…1) Tubuloglomerular Sclerosis [75] 2) Podocyte apoptosis 3) Produces fibrosis 4) Increases the production of extracellular matrix…”
Section: Role In Pathogenesis-[75]mentioning
confidence: 99%
See 1 more Smart Citation